KAJIAN KOMPOSISI KIMIA, NILAI NUTRISI, DAN ETNOFARMAKOLOGIS TANAMAN GENUS KENARI - Hamidah Rahman Rahman; Kusnandar Anggadiredja; Tutus Gusdinar; Johnner P Sitompul; A R Ryadin (Faculty of Pharmacy, Universitas Muslim Indonesia, 2019)
One species of canarium genus is Canarium indicum L which is an original plant from Indonesia. Utilization of some canarium nut species which spread around the world had been recognized, such as a source of nutritious food as well as its potency as raw material of medicine based on evidence-based scientific. In traditional medicine, was reported if canarium nut had been used for diabetes mellitus treatment, angina, hepatoprotective, anti-inflammatory, antirheumatic, expectorant, etc. This article aims to review the chemical composition, nutrient values, and potency of canarium nut as the raw material of medicine. Scientific data were obtained from online search results. From the searching was found that at least eight species of canarium nut reported which is related to chemical composition and its nutrition which also provide ethnopharmacological benefits. Overall results, all identified canarium nut species have a favorable chemical composition and nutritional values that can be utilized as functional, nutritional and medicinal food. Therefore, the result of this study also indicates if the canarium nut from Indonesia, C. indicum L., has not been thoroughly studied. That indicates by the lack of scientific paper which presented about C. indicum from Indonesia.